India: Mobility Trends - Teter, Wesley; Martin, Don (International Higher Education, 2014)
Over the past four years, US enrollments from India decreased 17 percent at graduate level and 16 percent at undergraduate level. As a top-sending country, the broader impact of these trends is substantial. However, new data and indicators point to a bright future beyond 2013. This article explores the latest trends in student mobility from India and key drivers for future growth. Key words: international student mobility, India, recruitment strategies, study in the US.